1982
DOI: 10.1288/00005537-198203000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Use of estrogen in treatment of familial hemorrhagic telangiectasia

Abstract: Within a 25 year period, 118 patients with a definitive diagnosis of familial hemorrhagic telangiectasia were treated for recurrent epistaxis. Twenty‐eight patients had dermoplasty but 67 patients received large dose estrogen therapy using ethinyl estradiol. The latter regime proved successful in every patient and the side effects and possible disadvantages of this treatment are considered in detail.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
9

Year Published

1986
1986
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 9 publications
0
63
0
9
Order By: Relevance
“…Bleeding from telangiectasias in the nose is one of the diagnostic criteria of mor bus Rendu-Osler-Weber [1], Bleeding disor ders such as von Willebrand's syndrome [2] and macroglobulinaemia Waldenstrom [3] are also associated with recurrent nose bleeds. It has been observed that children with allergy more often have recurrent nose bleeds than other children [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bleeding from telangiectasias in the nose is one of the diagnostic criteria of mor bus Rendu-Osler-Weber [1], Bleeding disor ders such as von Willebrand's syndrome [2] and macroglobulinaemia Waldenstrom [3] are also associated with recurrent nose bleeds. It has been observed that children with allergy more often have recurrent nose bleeds than other children [4].…”
Section: Introductionmentioning
confidence: 99%
“…3 Its effect, which is not immediate, seems to be estrogen dose-dependent and acts by enhancing microvascular circulation, coagulation, and vascular endothelial integrity. The most common combination schedule has been ethynil estradiol 0.01-0.05 mg and noresthisterone 1-3 mg. 4 This therapy should be used over six-month periods with pauses to reduce the incidence of adverse effects, mostly due to the estrogen component (vascular thrombosis, gynecomastia and loss of libido in men, breast tenderness and vaginal bleeding in women).…”
Section: Hormonal Therapymentioning
confidence: 99%
“…Die Familienanamnese ist für ca. 6-26% der erkrankten Heterozygoten negativ [16,42,45]. Die HHT ist genetisch heterogen, wobei 2 Gruppen unterschieden werden.…”
Section: Pathogeneseunclassified
“…So wurde eine gehäufte Zunahme von Teleangiektasien und Blutungen zum Beginn der Menopause oder in Zeiten verminderter Östrogenkonzentration beschrieben [6,16]. Auch wurde eine verminderte Epistaxisfrequenz bei Patientinnen mit HHT in der Schwangerschaft mitgeteilt [47].…”
Section: Hormontherapieunclassified
See 1 more Smart Citation